2020
DOI: 10.1007/s11356-020-09961-0
|View full text |Cite
|
Sign up to set email alerts
|

Low cost and effective reduction of formaldehyde in gross anatomy: long throw nozzles and formaldehyde destruction using InfuTrace™

Abstract: Formaldehyde is extraordinarily effective for fixation of human corpses and is routinely used in embalming solutions in anatomical dissection courses all over the world. High concentrations in vapors emitted from corpses embalmed with formaldehyde make it necessary to reduce the emission from cadavers for fulfilling tightening permissible exposure limits (PEL) worldwide. The study provides possible solutions to a problem faced by many anatomy labs. The emission of 50 human corpses was examined using 240 active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…This discrepancy could be due to differences in some characteristics such as dimensions of dissection halls or rooms, types of forced ventilation [ 23 ] and number of cadavers in the dissection rooms [ 21 ]. Recently, a study in Germany reported that using both improved ventilation and a polymerized FA method in dissection rooms kept the indoor air concentration below the critical values [ 34 ]. Table 2 shows the comparison of indoor FA concentrations among different studies with respect to some characteristics of the dissection rooms.…”
Section: Resultsmentioning
confidence: 99%
“…This discrepancy could be due to differences in some characteristics such as dimensions of dissection halls or rooms, types of forced ventilation [ 23 ] and number of cadavers in the dissection rooms [ 21 ]. Recently, a study in Germany reported that using both improved ventilation and a polymerized FA method in dissection rooms kept the indoor air concentration below the critical values [ 34 ]. Table 2 shows the comparison of indoor FA concentrations among different studies with respect to some characteristics of the dissection rooms.…”
Section: Resultsmentioning
confidence: 99%
“…A last aspect to consider here is the operating economy, both from an ecological and fiscal perspective. Air nozzles or ventilation slits 5,24 may offer advantages here. In consequence, an asymmetric installation of air ventilation systems in the mortuary and dissection laboratory should be critically considered to address the needs of chemical exposure, working comfort, tissue preservation, and operating economy.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, none of the anatomies surveyed from the DACH region responded that they would use chemical measures to lower an (existing) high formaldehyde exposure, e.g., using InfuTrace™ (American Bio-Safety, Rocklin, CA, USA) 5,40 or monoethanolamine. 41 The specific reason for this lack of use remains obscure.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations